SPATIAL AND TEMPORAL DISTRIBUTION INVESTIGATION OF SOLAR ENERGY POTENTIAL. APPLICATION: NUMERICAL AND MODELING STUDIES OF THE OPTIMAL EXPOSURE, THERMAL BEHAVIOR AND ENERGY PRODUCTION OF A PHOTOVOLTAIC INSTALLATION - Mohamed NFAOUI (Faculté des Sciences et des Techniques, Béni Mellal - Doctorat ou Doctorat National, 2021)
The study or applications of solar energy at a given site are dependent on more complete and detailed data on the solar radiation of this site, the knowledge of this deposit is of major interest to design and size solar energy systems. Thus, good sizing is possible only if the measurements are available continuously in space and time. The aim of this work is presented the method used in the calculation and describes the available data by trying to extract some useful information. In our study we use programs through MATLAB to estimate the totality of the solar radiation on any inclined surface. Moreover, we will study in the last part the influence of exposure (orientation and inclination) on the amount of solar radiation received on a surface of 1m2. Then in order to study the theoretical solar field available in Khouribga, a series of insolation and solar irradiation data calculate. We apply the same strategy of this work to the 20 Moroccan cities in different time scales (every 3min, every day, every month and all year). We also approach from a global perspective, allowing us to reach reliable and real results of the productivity of a PV installation under the shading effect. And among the objectives of this work is to studying the thermal behavior of a photovoltaic solar panel and the impact of the local ambient temperature, solar radiation and wind speed on the operating cell temperature of the photovoltaic modules in the region of Beni-Mellal Khenifra ". The first of all, we give a general and summary description of the meteorological data of the khouribga city concerning our study; under latitude of 33°41′09″ and Longitude of 7°22′58 ″, then we will approach in the second step a theoretical and experimental study, which explains the thermal behavior of a photovoltaic module from the influence of the cited parameters, as we present the equations adapted to the problem, then we can integrate the results found in two types of applications: the first; is to evaluate the performance of the hybridization of PV system with TEG generator through the electric power produced and to compare it with the PV system operating by itself under the weather conditions of Khouribga city. In the second; we studied this system for two cases, the case with solar tracker and the case with a fixed optimal angle. The last part of this manuscript, we suggest the theoretical calculation and the availability of solar radiation on the large spaces of all Moroccan territory.
Keywords: Solar Energy; PV installation; Optimal Tilt Angle; Operating Cell Temperature; PV-TEGgenerator.; 1. Natural Sciences; 1.3 Physical sciences